Liberia Early Childhood Development : SABER Country Report 2012 - World Bank (Washington, DC, 2014)
This report presents an analysis of the early childhood development (ECD) programs and policies which affect young children in the Republic of Liberia. It is part of a series of reports prepared by the World Bank using the systems approach for better education results (SABER)-ECD framework and includes analysis of early learning, health, nutrition, and social and child protection policies and interventions in Liberia, along with some regional and international comparisons. SABER-ECD identifies three core policy goals that countries should address to ensure optimal ECD outcomes: establishing an enabling environment, implementing widely, and monitoring and assuring quality.